Optimal Duration of Dual Antiplatelet Therapy After DES Implantation: A Meta-Analysis of 11 Randomized Trials. (March 2016) - Verdoia, Monica; Schaffer, Alon; Barbieri, Lucia; Montalescot, Gilles; Collet, Jean-Philippe; Colombo, Antonio; Suryapranata, Harry; De Luca, Giuseppe
Despite new-generations of drug-eluting stents (DESs), the optimal duration of dual antiplatelet therapy (DAPT) remains controversial. We performed a meta-analysis of randomized trials (RTs) evaluating the effectiveness and safety of shorter versus longer DAPT duration strategies in patients undergoing percutaneous coronary interventions with DES. Literature and main scientific session abstracts were searched. The primary end point was mortality. Secondary end points were (1) cardiovascular mortality, (2) nonfatal myocardial infarction, (3) definite/probable stent thrombosis (ST), and (4) major bleedings. We included 11 RTs (n = 32 372 patients). Shorter DAPT duration reduced mortality (odds ratio, OR [95% confidence interval, CI] = 0.85 [0.71-1], P = .05; p heterogeneity = 0.91). Similar results were observed when comparing 3 to 6 versus 12 months DAPT, while a significant increase in recurrent ischemic events was found for 6 to 12 months DAPT versus extended treatment (myocardial infarction: OR [95%CI] = 1.66 [1.37-2], P < .00001; phet = 0.13 and ST: OR [95%CI] = 2.47 [1.72-3.45], P < .00001; phet = 0.12), however, counterbalanced by a significant reduction in major bleeding (OR [95%CI] = 0.60 [0.47-0.76], P < .0001; phet = 0.38) and a trend in lower mortality. Thus, among selected patients undergoing DES implantation, a shorter DAPT strategy is associated with reduction in mortality and major bleeding but a higher risk of myocardial infarction and ST. A short duration (3-6 months) of DAPT appears as the safest strategy, while a prolonged duration (24-36 months) reduces thrombotic complications but with an excess in major bleeding complications.